Identification of flavone and flavanone from ethyl acetate fraction of Caesalpinia sappan heartwood and tentative structure-activity relationship: An in vitro and in silico approach - Andrian Sucahyo, Moh. Farid Rahman, Husnul Khotimah, Widodo Widodo, Siti Mariyah Ulfa (Journal of Applied Pharmaceutical Science, 2023)
Caesalpinia sappan, commonly known as secang in Indonesia, has been used in traditional medicine to treat inflammation, microbial infection, diabetes, and cancer. In this study, the chromatographic separation of the ethyl acetate fraction of C. sappan was carried out. It resulted in the isolation of 2′,5,6-trimethoxyflavone (TM) and cirsimaritin (CR), pinostrobin (PN), naringenin-5-methyl ether (NR), and alpinone (AL). All the compounds were elucidated and confirmed by LC-QToF-MS/MS. The in vitro antioxidant activity carried out by the 2,2-diphenyl-1- picrylhydrazyl method showed that all the compounds have potency as antioxidants. The tendency of antioxidative strength calculated from the ease of hydrogen transfer by density functional theory showed the activity order as follows: NR > PN > AL for subgroups of flavanone and CR > TM for subgroups of flavone, which have the same order as the in vitro result. In silico structure-activity relationships for the binding compounds to cytochrome P450 (CP450), lipoxygenase (LO), NADPH oxidase (NO), and xanthine oxidase (XO) were analyzed using the molecular docking and molecular dynamics techniques. The result revealed that the hydroxyl group of NR at the C-7 and C-4′ positions is crucial to interact with Val113 and Asn217 in the CP450. Furthermore, the absence of the hydroxyl group at the C-3 position of PN shows better binding energy (ΔG = −4.05 kcal/mol) compared to AL (ΔG = −1.7 kcal/mol) in the LO. Double bonds at the C-2 and C-3 positions maintain the interaction with Asp179 of the NO receptor. For the XO receptor, two methoxy groups at the C-6 and C-5 positions (TM) are important to interact with a key residue like Arg880. Taken together, the result suggests that the flavone and flavanone derivatives from C. sappan have a potent antioxidant activity that could be useful in combating oxidative stress in the human body.
Keywords: Flavonoid, flavone, flavanone, oxidative reaction, DPPH, molecular docking